Promotional management or privatization of the urban planning management? puerto madero urban project, buenos aires - argentina (2008)
The article is founded on the Doctoral Thesis, The Mixed City-planning Management in Central Cities: A study on the intervention in urban voids, presented to the Faculty of Architecture, Design and Urbanism of the University of Buenos Aires. The methodological profile is qualitative, centered in the study of case from field work, research on previous circumstances and interviews to the involved actors. More specifically, it approaches to the task of the urban project in Argentina, it seeks out on the question of Urban Project as present in the model of promotional management of interventions at an international level or, on the contrary, it just represents a spoiled attempt of application.